Creation of a MOOC and an Augmented Reality application on exoplanets for the Exoplanets-A project. Issue Volume 15:Issue S367(2019) (December 2019) - de Assis Peralta, R.; Minier, Vincent; Lagage, Pierre-Olivier
Abstract: The European Exoplanets-A project aims to provide a comprehensive view of the nature of exoplanet atmospheres, through an interdisciplinary approach. Exoplanets-A includes a knowledge server where we provide the scientific results and educational resources gathered and developed during the project. In this proceedings, we present two such educational resources: a MOOC and an augmented reality application.